Inculcating Islamic values in teaching western short stories to Muslim learners - Othman, Khairiah; Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Sarudin, Isarji (IIUM Press, 2011)
Muslim scholars advocate that Islamic values should be inculcated in every discipline. English language teaching is no exception as it has been infused with the values of the West, as reflected in Western instructional materials. This is inevitable as language is a carrier of culture and therefore, language and culture are intertwined and inseparable. This study was conducted to investigate Muslim teachers’ inculcation of Islamic values in the teaching of Western short stories. Data were collected using document analysis, interviews and classroom observations. The findings of the study indicated five recurring themes employed by Muslim teachers in teaching these texts to Muslim students. The teachers highlighted unIslamic practices, used Islamic concepts and Islamic Arabic terms, related the texts to stories of the prophets, discussed current Muslim related issues and finally, made references to the Quranic verses and Hadith. This paper has implications for theory, practice and policy.